A Predictive Model for Estimating Reservoir Impounding Time Based on the Net Inflow and Storage Volume - Harimukti Rosita R.; Pitojo T. Juwono; Lily M. Limantara; Emma Yuliani (Journal of Human, Earth, and Future)
This research aims to develop a duration model for predicting the rise in water level during the initial impounding phase of a reservoir (from bed elevation to the normal storage volume elevation). The initial impounding of a reservoir represents the first test following the completion of dam construction, during which the reservoir begins to function as intended. Therefore, the expected outcome of this research is to formulate a model that estimates the duration required to fill the reservoir to its designated storage level. The study is conducted on 10 reservoirs. The methodology involves analysing existing conditions (based on observed data from initial impounding in several reservoirs), identifying influential variables, and developing a predictive model for reservoir impounding duration. The research begins with a review of elevation data recorded during the impounding process across selected reservoirs. Field data are filtered to extract continuous daily elevation records from reservoirs that underwent a single-stage impounding process. A linear regression model is employed to predict the duration of reservoir impounding, as it provides clear, interpretable results and supports accurate decision-making during the implementation phase. By using the base equation of linear regression: Ln(D)=m×Ln(S)+n×Ln(Inet) and based on the analysis result of 28 combinations, there is selected the combination with the best determination coefficient (R2) that is 0.99 with m = 1.047 and n = -1.08807. After being carried out the verification to 4 locations of dams that are processing the reservoir impounding, it is produced good determination coefficient and it is near to 1, so there is obtained the linear regression equation for analyzing the impounding time by using data of reservoir storage volume (S) and net inflow (net inflow = inflow to reservoir – outflow from reservoir during the impounding process) as follows: Ln(D(rl))=1.047×Ln(S)+(-1.08807)×Ln(Inet).